2009
DOI: 10.1080/01616840902892390
|View full text |Cite
|
Sign up to set email alerts
|

Library and Information Services to the Arabic‐Speaking Community: A Survey of Michigan Public Libraries

Abstract: Public Libraries tout that they serve diverse communities, even having collection development policies, programs, and service that recognize their dissimilar neighborhoods. The authors of this article, having noted the influx of Arab-speaking populations from Iraq and other Middle East countries to the United States, sought to find out the extent to which this population was receiving library service. The investigators discovered that four Michigan counties comprise a significant Arab-speaking population; in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Al-Qallaf and Mika surveyed public libraries in Michigan about their collections, circulation patterns, and collection development policies for Arabic speakers. 101 The authors identified the lack of age-appropriate Arabic language material as a problem for public libraries serving this population.…”
Section: Collection Development and Selectionmentioning
confidence: 99%
“…Al-Qallaf and Mika surveyed public libraries in Michigan about their collections, circulation patterns, and collection development policies for Arabic speakers. 101 The authors identified the lack of age-appropriate Arabic language material as a problem for public libraries serving this population.…”
Section: Collection Development and Selectionmentioning
confidence: 99%